C-Reactive Protein in Arrhythmogenic Right Ventricular Dysplasia/Cardiomyopathy and Relationship with Ventricular Tachycardia. (9th August 2010) - Bonny, Aimé; Lellouche, Nicolas; Ditah, Ivo; Hidden-Lucet, Françoise; Yitemben, Martial T.; Granger, Benjamin; Larrazet, Fabrice; Frank, Robert; Fontaine, Guy
Abstract : Background . The relationship between C-reactive protein (CRP) elevation and ventricular tachycardia (VT) in arrhythmogenic right ventricular dysplasia/cardiomyopathy (ARVD/C) is unclear. Methods and Results . In 91 consecutive patients with either ARVD/C with or without VT (cases) or idiopathic right ventricular outflow tract (RVOT) tachycardia (controls), blood sampling were taken to determine CRP levels. In ARVD/C patients with VT, we analyzed the association between VT occurrences and CRP level. Sixty patients had ARVD/C, and 31 had idiopathic RVOT VT. Patients with ARVD/C had a significant higher level of CRP compared to those with RVOT VT (3.5 ± 4.9 versus1.1 ± 1.2  mg/l, P = .0004 ). In ARVD/C group, 77%, (n = 46 ) patients experienced VT. Of these, 37% (n = 17 ) underwent blood testing for CRP within 24 h after the onset of VT and the remaining 63% (n = 29 ) after 24 h of VT reduction. CRP level was similar in ARVD/C patients with or without documented VT (3.6 ± 5.1  mg/l versus3.1 ± 4.1  mg/l, P = .372 ). However, in patients with ARVD/C and documented VT, CRP was significantly higher when measured within 24 hours following VT in comparison to that level when measured after 24 h (4.9 ± 6.2  mg/l versus3.0 ± 4.4  mg/l, P = .049 ). Conclusion . Inflammatory state is an active process in patients with ARVD/C. Moreover, there is a higher level of CRP in patients soon after ventricular tachycardia, and this probably tends to decrease after the event.